Criar forças é criar Quilombos: boxeadoras, coletividade tática e ativismo comunitário de jovens negras no Brasil - Antônia Gabriela P. de Araújo (Les Cahiers ALHIM)
This paper will, from reflections on issues of racial geographies and black women in the African Diaspora, emphasize the performance of black girls' feminism and community activism in the favelas of Rio de Janeiro, Brazil through a martial art arena, boxing. Gender and race relations will be discussed intertwined with issues of peripheral feminisms, sports politics and activism, since these black women are boxers and active in their communities through their professions as athletes. The plot is made through daily situations involving these boxers and their ways of producing communities, bodies, and feminist political projects in the peripheries.